The Use of Life Insurance in Estate Planning - Hiram H. Lesar (Washington University Law Quarterly, 1958)
The principal role of life insurance, the type of insurance with which estate planning is primarily concerned, is to provide liquid funds to pay the costs of dying. These include, in addition to debts, administration and funeral expenses, expenses of the last illness, taxes, and the care of dependents. When one reflects that insurance is an asset which is as liquid as cash and yet is an earning asset, that it is worth more at death when needed and that the increase in value above the amount of premiums paid is not subject to the income tax, its importance in meeting these expenses is apparent. In determining how best to utilize the assets of an estate, then, careful consideration must be given to the disposition of insurance. But beyond the problem with respect to the use of existing assets, one needs to be aware of the various specific uses to which insurance may be put. There is evidence that not enough estate owners and their advisers have been aware of the possibilities. These perhaps can best be presented by considering small estates first, and then larger estates. Before so discussing the subject, however, it seems advisable to describe briefly the kinds of insurance and the types of settlement options available under the policies.
Keywords: Estate planning; Life insurance